Rotorcraft Loss of Control In-Flight - The need for research to support increased fidelity in flight training devices, including analogies with upset recovery for fixed-wing aircraft - White, M.D.; Padfield, G.D.; Lu, L.; Advani, S. (My University, 2018)
A review of the worldwide commercial jet fleet accident data, 2001 - 2010, showed that the largest single factor leading to fatalities was Loss of Control In-Flight (LOC-I). 20 such accidents occurred during this timeframe with over 1800 fatalities [1], highlighting the need for research to investigate the causes of this problem and to develop new regulations and training programmes to improve flight safety.